Association of oxidative stress and memory performance in postmenopausal women receiving estrogen-progestin therapy - Shafin, Nazlahshaniza; Zakaria, Rahimah; Hussain, Nik Hazlina Nik; Othman, Zahiruddin (The North American Menopause Society, 2013)
Objective: The aim of this study was to examine the association between changes in blood oxidative stress level/ activity and changes in memory performance among postmenopausal women. Methods: This study involved 39 postmenopausal women who received estrogen-progestin therapy (EPT) for 16 weeks. Verbal learning and memory performance were assessed using the Malay Version of Auditory Verbal Learning Test before and after 16 weeks of EPT. Oxidative stress levels/activities before and after 16 weeks of EPT were determined using commercially available kits. Data were analyzed using paired t test and r. P G 0.05 was considered significant. Results: The activities of glutathione peroxidase and catalase were considerably increased (P G 0.05), but the level of 4-hydroxynonenal was notably decreased (P G 0.05), after 16 weeks of EPT. There were positive correlations between changes in plasma superoxide dismutase and changes in trial A2 scores (r = 0.36, P G 0.05), and between changes in the ratio of blood reduced glutathione to oxidized glutathione and changes in trial A2 scores (r = 0.34, P G 0.05). Conclusions: Sixteen weeks of EPT increase blood antioxidant capacity. However, most of the changes in oxidative stress level/activity are not significantly associated with changes in the memory performance of postmenopausal women.